The Pied piper - Shute, Nevil, 1899-1960. (London : Vintage, 2009)
Presents a retelling of the story of the Pied Piper, a mysterious man brought in to save the village of Hamelin from being overrun by rats,and who exacts a terrible revenge when the townspeople refuse to pay him.
5-8.
Keywords: Fairy tales; Fairy tales